Función ejecutiva y entrenamiento computarizado en niños de 7 a 12 años con discapacidad intelectual (2017)
ABSTRACT: A comparative study of executive function (planning and flexibility components) presented by a computerized cognitive training program applied to children with intellectual disabilities. Few studies found on intervention in population with intellectual disabilities involving computer programs about executive functioning, and focused on neuropsychological processes as educational support. In this study, a population sample of 20 boys and girls in Antioquia (Colombia) diagnosed with intellectual disabilities, between 7 and 12 years of age, divided into an experimental group (10) and a control group (10) was used. The study used a pretest-posttest design; the case group had a training process with the computer software Lumosity for 15 sessions, 3 times a week, with an intensity of 40 minutes each (20 for flexibility and 20 for planning) as components of executive function. Comparing these components of executive function (before and after the process), in the case group and the control group are significant results that demonstrate the generation change in the components of planning and flexibility in this population; It is also possible to validate the effectiveness of computerized cognitive training programs.